2005
DOI: 10.1021/es051858x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of C7F15COOH (PFOA) and Other Perfluorocarboxylic Acids during the Atmospheric Oxidation of 8:2 Fluorotelomer Alcohol

Abstract: Calculations using a three-dimensional global atmospheric chemistry model (IMPACT) indicate that n-C8F17CH2CH2OH (widely used in industrial and consumer products) degrades in the atmosphere to give perfluorooctanoic acid (PFOA) and other perfluorocarboxylic acids (PFCAs). PFOA is persistent, bioaccumulative, and potentially toxic. Molar yields of PFOA depend on location and season, are in the range of 1-10%, and are of the correct order of magnitude to explain the observed levels in Arctic fauna. Fluorotelomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
233
3
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(249 citation statements)
references
References 14 publications
12
233
3
1
Order By: Relevance
“…Wang et al [3] calculated the mass flux of PFCAs in the global transport processes and suggested that historical direct emissions from manufacture and consumer usages were the major contributors of PFCAs detected in the environment. However, the indirect contributions via the biodegradation and biotransformation of polyfluoroalkyl precursors and atmospheric oxidation have also been confirmed by model prediction [9], laboratory experiments [10,11] and environmental monitoring [12]. Laboratory systems utilizing microbialconsortium and animal models to study polyfluoroalkyl-precursor biotransformation provided insight to understand the extent of contributions of such precursors to PFCAs and PFSAs detected in the environment and biota.…”
Section: Introductionmentioning
confidence: 87%
“…Wang et al [3] calculated the mass flux of PFCAs in the global transport processes and suggested that historical direct emissions from manufacture and consumer usages were the major contributors of PFCAs detected in the environment. However, the indirect contributions via the biodegradation and biotransformation of polyfluoroalkyl precursors and atmospheric oxidation have also been confirmed by model prediction [9], laboratory experiments [10,11] and environmental monitoring [12]. Laboratory systems utilizing microbialconsortium and animal models to study polyfluoroalkyl-precursor biotransformation provided insight to understand the extent of contributions of such precursors to PFCAs and PFSAs detected in the environment and biota.…”
Section: Introductionmentioning
confidence: 87%
“…Additionally, Wallington et al (2006) calculated a 8:2 FTOH concentration of around 4 × 10 5 molecule/m 3 at 50 m above the sea level in July, which corresponded to a concentration of about 308 pg/m 3 , in the air of Bohai and Yellow Sea by modeling. The concentrations were in the range of the monitoring data in this study.…”
Section: Distributions Sources and Gas Phase Dry Deposition Of Neutmentioning
confidence: 99%
“…2 In addition to their presence in various perfluorinated products, PFOS and PFOA are also stable degradation products/metabolites of neutral PFCs. These precursor compounds are more volatile, 5 and therefore more likely to undergo LRAT, with sufficient atmospheric lifetimes to reach remote locations, 6 where they can break down. Possible precursor compounds for other chain-length perfluorocarboxylates (PFCAs) and PFOS are fluorotelomer alcohols (FTOHs) 2 and fluorooctane sulfonamides/ethanols (FOSAs/FOSEs), 7,8 respectively.…”
Section: ' Introductionmentioning
confidence: 99%